Cognitive Load and Language Switching in Urdu-English Bilingual Classrooms: A Qualitative Exploration of Teaching Strategies in Pakistani Secondary Schools - Abdul Ghafoor; Amjad Islam (Dialogue Social Science Review (DSSR), 2025)
This qualitative study explores the interplay of cognitive load and language switching in Urdu-English bilingual classrooms in Pakistani secondary schools, addressing a critical gap in non-Western bilingual education research. Grounded in Cognitive Load Theory, it examines the cognitive demands of switching between Urdu and English and the teaching strategies that mitigate these challenges. Data from semi-structured interviews with 10 teachers and 20 students, alongside classroom observations in Sahiwal, reveal that task complexity, particularly in linguistically demanding subjects like mathematics and science, significantly increases cognitive load. Teachers employ strategies such as scaffolding, simplified instructions, and visual aids to reduce cognitive overload, with most students reporting comfort with strategic code-switching, though 25% feel overwhelmed by frequent switches. These findings underscore the need for balanced language switching and tailored pedagogical approaches to optimize learning outcomes. Implications for educators and policymakers include designing curricula that account for cognitive demands and training teachers in effective bilingual strategies.